Art is not what you think it is - Preziosi, Donald, 1941-; Farago, Claire J. (Hoboken : John Wiley & Sons, 2012)
Art Is Not What You Think It Is utilizes original research to present a series of critical incursions into the current state of debate on the idea of art, making manifest what has been largely missing or unsaid in those discussions. Links museology, history, theory, and criticism to the realities of contemporary social conditions and shows how they have structurally functioned in a variety of contexts. Deals with divisive and controversial problems such as blasphemy and idolatry, and the problem of artistic truth. Addresses relations between European notions about art and artifice and those develop.
Art Is Not What You Think It Is; Contents; List of Figures; Preface: Art Is Not What You Think It Is; Acknowledgments; Introduction: Art and/as Manifesto; First Incursion: Artistry and Authorship; Second Incursion: The Dangers of Art and the Trap of the Visual; Third Incursion: To See the Frame that Blinds Us; Fourth Incursion: Deconstructing the Agencies of Art; Fifth Incursion: Intersections of the Local and the Global; Sixth Incursion: Into the Breach of Art and Religion; Seventh Incursion: The Art of Commodifying Artistry; Index.
Print version record.
Keywords: Art; Fine Arts; ART -- General; Art; Electronic books